The Role and Patterns of Coordination in Arabic Learning - Hamdy, Mohammad Zainal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Teachers are leaders in the teaching process and have an important influence on shaping learners' behavior. Therefore, teachers not only teach and learn, but also educate and supervise learners in all processes. In order to complete his work and responsibilities, an Arabic teacher must have excellent language skills and be proficient in a variety of sciences so that learners can influence cognitive, emotional and behavioral aspects.The research method that the researcher used here means the descriptive qualitative method in Library research. The school should set the studied goals to facilitate all individuals to measure their achievement. Therefore, the development of planning and organization, whether the teaching or the curriculum is an obligatory matter for him. And also to benefit his role in order to increase the professional competence of other teachers. It is known that coordination has the main role, which is to develop the process of integration of the teacher's personnel, to upgrade his ability and performance, to develop the curriculum, and to conduct research to correct the teaching process.